The efficacy of silver needle therapy for treating low back pain: a protocol for meta-analysis of randomized controlled trials - Li, Wangyu; Xu, Xueru; Liu, Rongguo (Frontiers in Medicine, 2024)
Background: As population aging and unhealthy living habits may exacerbate the prevalence and burden of low back pain(LBP), effective treatment and improvement of patient quality of life are particularly critical. Silver needle therapy(SNT), having evolved from traditional acupuncture, involves placing silver needles into muscles, tendons, and fascia for treatment. However, it still lacks robust clinical evidence to substantiate its effectiveness. Therefore, it is necessary to conduct systematic reviews and meta-analyses to evaluate the clinical efficacy of SNT for treating LBP..We will search PubMed, Medline, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang Databases up until December 2023 to identify randomized controlled trials of SNT treatment in adult patients with LBP. The primary outcome will be the intensity of pain after pain management. Secondary outcomes will include the Oswestry Disability Index, Japanese Orthopedic Association Back Pain Evaluation Questionnaire, requirement for analgesic drugs, and treatment-related adverse reactions. Two reviewers conducted the literature search, selected studies that might meet the inclusion criteria based on the title and abstract, and extracted data from the eligible literature independently and will independently assess the risk of bias using the Revised Cochrane Risk-of-Bias (RoB2) tool. Multivariate analyses (including subgroup analysis, trial sequential analysis (TSA), sensitivity analysis, etc.) will be conducted to improve the quality of evidence.Registration number: CRD42023466207.